Impact of structured education on glucose control and hypoglycaemia in Type-2 diabetes: a systematic review of randomized controlled trials - Yorke, Ernest (Ghana Med J, 2018)
Evidence for the use of structured education in diabetes management is accumulating and has shown positive influence in the management of Type-2 diabetes. OBJECTIVE: To assess the impact of structured education on glucose control and hypoglycaemia in the management of Type-2 diabetes. METHODS: A systematic review was done using Medline via Ovid and EMBASE databases of published English literature between 1980 and 2014. Included studies were randomized control trials that assessed the impact of structured education on glucose control and hypoglycaemia. RESULTS: Out of the 12,086 full text articles were identified, 36 full text articles were finally considered for this review after applying both inclusion and exclusion criteria, of which 34 were exclusively on the effect of structured diabetes education on glucose control whilst 2 were studies on the effects of structured diabetes education on glucose control and hypoglycaemia. Majority of the studies included a predominant Caucasian population. There was heterogeneity in the included studies such as intervention methods and intensity as well as follow up periods. Group based education was preferred over individual education by most studies. Overall, most of the studies showed a significant positive effect on glycaemic control compared with control groups. One study showed a significant impact of structured education on hypoglycaemia. CONCLUSION: Structured education has positive impact on glucose control and hypoglycaemia in Type-2 diabetes and must be incorporated in routine care. FUNDING: The study was funded by the authors